Posthumous interests of a person - Jędrczak, Stanisław (Hybris, 2018)
Does the interest of a person go beyond the limits of her life? In the article we advocate the realistic view, proclaiming that interests of a person continues even after her death. In contemporary philosophy the realistic view of the post-mortem interests, already outlined by Aristotle, had been delivered by Joel Feinberg. The paper associates an ontological thread with a moral philosophy and general reflection on the notion of a person. Developing the Timothy Chappell’s idea, we introduce the term of personal stance, which is an aspect of the proleptic nature of the concept of a person. Since personal stance includes also a dead person, she belongs to the primary moral constituency. This fact clarifies our concern for the posthumous fate. Lastly, we argue that in the light of private law posthumous interests are to be understood as personal rights.